Pressurised objects technical condition evaluation with limited access to surface using acoustic emission method - A. I. Gnevko; O. E. Zubov; S. V. Grazion; M. V. Mukomela; V. A. Kobzev (Научный вестник МГТУ ГА)
The article deals with the use of a known method of acoustic emission to assess the technical condition of working under pressure, with limited access to the surface of the object under control. This reduces the cost of time and money and increases reliability of the test results. The advantage of this method is confirmed by gasifiers technical condition evaluation example.